Pengaruh Ekstrak Daun Kedondong (Spondias dulcis)Terhadap Pertumbuhan Trichophyton rubrum Secara In Vitro: Effect of Kedondong (Spondias dulcis) Leaf Extract on In Vitro Growth of Trichophyton rubrum - Nirosa, Givari Dwi; Puspitasari, Puspitasari (Medicra (Journal of Medical Laboratory Science/Technology), 2019)
Dermatophytes are fungi that can cause dermatophytosis, this fungus attacks the skin of the stratum corneum. This study aims to determine the effectiveness Spondias dulcis leaf extract on the growth of Trichophyton rubrum in vitro. This research uses Trichophyton rubrum and Spondias dulcis leaf extract. The treatment in this study was divided into 6 treatment groups, namely negative control, concentration of 20%, 40%, 80%, 100% and positive control, as well as 4 repetitions. After incubation for 5-7 days then observations were made and the results showed that Spondias dulcis leaf extract with various concentrations did not have different results, there was no effect on the growth of Trichophyton rubrum in vitro. Negative control used 10% DMSO solution which showed no effect on the growth of Trichophyton rubrum. On positive control using terbinafine antifungal drugs showed results that were very influential on the growth of Trichophyton rubrum. So it can be concluded that Spondias dulcis leaf extract has no influence on the growth of Trichophyton rubrum.